Students’ Perceptions of their First Practice Placement in Early Childhood Care and Education - Walsh, Orla (International Journal of Practice-based Learning in Health and Social Care, 2016)
It is widely accepted in higher education that practice placements facilitate students’ professional development by providing a beneficial learning environment, the chance to experience the ‘world of work’ and to develop the skills of a competent practitioner. However, the transition from college to practice placement, adjusting to new learning environments and managing workload demands can be challenging for students. This paper explores some of these issues. It investigates students’ perceptions regarding their first practice placement on an Early Childhood Care and Education programme in a third-level college in the Republic of Ireland. The study examines students’ views on specific aspects of placement, including preparation, management of the assessment portfolio and reflective journal, experience of supervision and opportunities for acquiring new skills and competencies. A self-administered, non-experimental survey, comprising closed and open questions, was utilised to allow the gathering of specific statistical information (quantitative) as well as students’ views and opinions (qualitative) of placement experiences. The findings indicate that the first practice placement was, in general, a positive experience, whereby students enjoyed opportunities to work with children and link theory to practice. However, it was found that there were difficulties in a) writing regular journal entries and reflective writing, b) completing child observations and c) implementing a planned intervention. A substantial number struggled with portfolio workloads together with other placement duties.